On the lookout for a potential antagonist against Cryptostroma corticale—an insight through in vitro dual culture studies - Schlößer, Rebekka; Bien, Steffen; Bußkamp, Johanna; Langer, Gitta Jutta; Langer, Ewald Johannes (Frontiers in Forests and Global Change, 2025)
In an effort to find a potential antagonist for Cryptostroma corticale, the causal agent of the sooty bark disease, different fungi previously isolated from Acer pseudoplatanus were tested in dual culture antagonism assays with C. corticale. In total 102 fungal strains, mainly Ascomycota, were tested. Each potentially antagonistic strain was paired with three different strains of C. corticale. Four different tests were conducted to get a better understanding of the interactions between C. corticale and the potential antagonists. Test 1 was a dual culture set up at room temperature with all 102 strains to get an overview of the interactions with C. corticale, as well as placing the potential antagonist on a Petri dish 1 week prior to C. corticale for a selection of fungi. For Test 2, only fungi which showed inhibition at distance in Test 1 were chosen and tested on different media at 25°C, the optimal growing temperature of the pathogen. In Test 3, fungi showing signs of antagonism in Test 1 were tested against C. corticale in a 6:1 ratio of potential antagonist plugs to the C. corticale plug. For Test 4, the viability of C. corticale hyphae was tested after they stopped growing in dual culture with a potential antagonist. These in vitro trials show that C. corticale displays a very competitive behavior, overgrowing most of the tested fungi. However, nine of the tested fungal strains, showed an antagonism at distance for at least one of the C. corticale strains. Over all tests, Hypholoma fasciculare, Jackrogersella cohaerens, Paracamarosporium cf. fagi, Pezicula sporulosa, and Preussia cf. aemulans showed the highest potential in regard of functionality as a biological control agent.